2016
DOI: 10.1590/0074-02760150303
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Cryptosporidium identified in clinical samples from cities in Brazil and Argentina

Abstract: The identification and characterisation of Cryptosporidiumgenotypes and subtypes are fundamental to the study of cryptosporidiosis epidemiology, aiding in prevention and control strategies. The objective was to determine the genetic diversity ofCryptosporidium in samples obtained from hospitals of Rio de Janeiro, Brazil, and Buenos Aires, Argentina. Samples were analysed by microscopy and TaqMan polymerase chain reaction (PCR) assays forCryptosporidium detection, genotyped by nested-PCR-restriction fragment le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 52 publications
4
21
1
12
Order By: Relevance
“…In England, this subtype has been also identified in humans (Chalmers et al 2011), strongly suggesting a zoonotic transmission risk. In contrast, a recent study carried out in Argentinean and Brazilian persons, C. hominis was frequently detected (Peralta et al 2016) and none of C. parvum subtypes reported in this study were found. Further research is required to understand the real clinical significance of each C. parvum subtype, as well as their interaction when co-infections occur.…”
Section: Dairy Herdcontrasting
confidence: 99%
“…In England, this subtype has been also identified in humans (Chalmers et al 2011), strongly suggesting a zoonotic transmission risk. In contrast, a recent study carried out in Argentinean and Brazilian persons, C. hominis was frequently detected (Peralta et al 2016) and none of C. parvum subtypes reported in this study were found. Further research is required to understand the real clinical significance of each C. parvum subtype, as well as their interaction when co-infections occur.…”
Section: Dairy Herdcontrasting
confidence: 99%
“…Turning our attention now to enteric parasitic infections in dogs, poor Brazilian populations usually neglect the treatment of infections in their dogs, particularly because of the low purchasing power and low awareness of the risk of zoonosis transmission [3,[44][45][46]. We observed that low income impacts the cultural aspect of animal health management.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 86%
“…The genus Cryptosporidium consist of over 20 species which species like C. parvum from C. hominis are indistinguishable morphologically (Peralta et al, 2016). Cryptosporidium infection in both immunocompromised and immunocompetent individuals may be found by different species and genotypes (Cama et al, 2007).…”
Section: Prevalence Of Intestinal Parasitic Infection In Cancer Orgamentioning
confidence: 99%